Dual therapy with an oral non-vitamin K antagonist and a P2Y12 inhibitor vs triple therapy with aspirin, a P2Y12 inhibitor and a vitamin K antagonist for the treatment of diabetes mellitus patients with co-existing atrial fibrillation following percutaneous coronary intervention: A meta-analysis. Issue 15 (16th April 2021) - Wang, Qiang; Yang, Keping
Abstract: Background: In this analysis, we aimed to compare the efficacy and safety of dual therapy (DT) with a non-vitamin K oral anticoagulant (NOAC) and an adenosine diphosphate receptor antagonist (P2Y12 inhibitor) vs triple therapy (TT) with aspirin, a P2Y12 inhibitor and a vitamin K antagonist for the treatment of diabetes mellitus (DM) patients with co-existing atrial fibrillation (AF) following percutaneous coronary intervention (PCI). Methods: Medical Literature Analysis and Retrieval System Online (MEDLINE), http://www.ClinicalTrials.gov, Excerpta Medical data BASE (EMBASE), Web of Science, Cochrane Central and Google Scholar were the searched databases. Studies that were randomized trials or observational studies comparing DT vs TT for the treatment of DM patients with co-existing AF following PCI were included in this analysis. The adverse cardiovascular outcomes and bleeding events were the endpoints. This meta-analysis was carried out by the RevMan version 5.4 software. Risk ratios (RR) with 95% confidence intervals (CI) were used to represent data and interpret the analysis. Results: A total number of 4970 participants were included whereby 2456 participants were assigned to the DT group and 2514 participants were assigned to the TT group. The enrollment period varied from year 2006 to year 2018. Our current results showed that major adverse cardiac events (RR: 1.00, 95% CI: 0.84–1.20; P = .98), mortality (RR: 1.08, 95% CI: 0.78–1.48; P = .66), myocardial infarction (RR: 1.02, 95% CI: 0.74–1.42; P = .90), stroke (RR: 0.94, 95% CI: 0.53–1.67; P = .84) and stent thrombosis (RR: 1.09, 95% CI: 0.56–2.10; P = .80) were similar with DT versus TT in these patients. However, the risks for total major bleeding (RR: 0.66, 95% CI: 0.54–0.82; P = .0001), total minor bleeding (RR: 0.74, 95% CI: 0.64–0.85; P = .0001), Thrombolysis in Myocardial Infarction (TIMI) defined major bleeding (RR: 0.58, 95% CI: 0.35–0.95; P = .03), TIMI defined minor bleeding (RR: 0.62, 95% CI: 0.42–0.92; P = .02), intra-cranial bleeding (RR: 0.34, 95% CI: 0.13–0.95; P = .04) and major bleeding defined by the International Society on Thrombosis and Hemostasis (RR: 0.68, 95% CI: 0.51–0.90; P = .008) were significantly higher with TT. Conclusions: DT with a NOAC and a P2Y12 inhibitor was associated with significantly less bleeding events without increasing the adverse cardiovascular outcomes when compared to TT with aspirin, a P2Y12 inhibitor and a Vitamin K antagonist for the treatment of DM patients with co-existing AF following PCI. Hence, DT is comparable in efficacy, but safer compared to TT. This interesting hypothesis will have to be confirmed in future studies.